ALIGNING TAX PLANNING AND CSR STRATEGY TO BOOST FIRM VALUE: THE MODERATING POWER OF FEMALE BOARD REPRESENTATION - Boli, Hubertus Ade Resha Raditya (E-Jurnal Akuntansi TSM, 2025)
This research examined the effect of tax planning and corporate social responsibility (CSR) strategy on firm value, with board gender diversity (BGD) as a moderating variable. This study used a quantitative approach with secondary data from 43 food and beverages companies listed on the Indonesia Stock Exchange (IDX) during 2020-2024, resulting in 215 firm-year observations. Data were analyzed using multiple linear regression and moderated regression analysis (MRA) with STATA 19 software. The results showed that both tax planning and CSR strategy had a positive and significant effect on firm value, indicating that transparent fiscal management and responsible CSR practices improve market performance. However, board gender diversity did not significantly moderate the relationship between tax planning and firm value but positively moderated the relationship between CSR strategy and firm value. This research contributes to the literature on corporate governance and sustainability by integrating tax behavior, CSR, and board diversity as determinants of firm value, and it provides practical insights for policymakers and corporate leaders to align governance structures with sustainable growth goals.